2011
DOI: 10.1111/j.1460-9592.2011.03525.x
|View full text |Cite
|
Sign up to set email alerts
|

An audit of laryngoscopes and application of a new ISO standard

Abstract: Laryngoscope light should be regularly audited. Results from these audits can be used to retire or repair substandard laryngoscopes to maintain acceptable standards of laryngoscope light. Audit results produce tangible evidence that is useful when applying for capital expenditure. Light measurements are not easy to make. There needs to be a convenient device to reliably measure laryngoscope illumination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
1
8
0
1
Order By: Relevance
“…1,2,7 Another children's hospital audit of 18 anesthesia department laryngoscopes found that half did not meet these literature standards, and only 1 device met the ISO standard. 8 In a manikin study, a group of anesthesiologists found only 1 of 16 laryngoscopes produced the median acceptable light on each reading and the minimum acceptable light for all testers. 9 In most cases, the amount of light required to intubate an airway is less than that required for an otolaryngologist to characterize airway pathologic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,7 Another children's hospital audit of 18 anesthesia department laryngoscopes found that half did not meet these literature standards, and only 1 device met the ISO standard. 8 In a manikin study, a group of anesthesiologists found only 1 of 16 laryngoscopes produced the median acceptable light on each reading and the minimum acceptable light for all testers. 9 In most cases, the amount of light required to intubate an airway is less than that required for an otolaryngologist to characterize airway pathologic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The ISO 7376:2009 standard describes limits for the distribution of light as well as the illuminance. A published audit of laryngoscope xenon bulb light illuminance and spread found that out 18 disposable laryngoscopes, none complied with the ISO standard for light distribution [5]. Whilst this audit used different manufacturers and different bulbs, the case study and image presented show the light distribution is clearly scattered unevenly with the McGrath ® MAC.…”
Section: Discussionmentioning
confidence: 90%
“…For manufacturers of laryngoscopes the International Organisation for Standardisation (ISO) recommends a minimum level of 500 lux for at least 10 minutes [2]. A published audit of laryngoscope xenon bulb light illuminance and spread found that out 18 disposable laryngoscopes, none complied with the ISO standard for light distribution [5]. The images in the figure show a more confluent and dense light from the ProAct ® Metal Max compared with the McGrath ® MAC (figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…13 A study by Murphy et al 7 of 691 laryngoscopes found that 28% did not meet the minimum required 500 lux at 10 minutes. Baker et al 14…”
Section: Introductionmentioning
confidence: 99%